(untitled) (Physical Education, Health and Social Sciences, 2025)
Violence and strife are realistically shown in online games. This study delves at the ways radicals impact gamers through various forms of media. One possible source of fuel for media warfare is the normalization of violence in video games through their narratives and interactions. Addiction to online gaming is on the rise in Pakistan, especially among adults who use it as a way to escape from every day stressors. To further understand the phenomenon and how it affects family functioning and self-control, this study will take a quantitative approach, conduct a survey with adults who are currently battling an addiction to internet gaming. The results of the study will shed light on the origin, effects, and potential remedies of adult’s addiction to online gaming in Pakistan. It is intended that the findings of this study would aid in the creation of efficient therapies to address the problem and enhance family functioning and the capacity for self-control in addicts. A self-administered questionnaire was utilized to gather information from 400 adult’s gamers, ages 18 to 40, using a cross-sectional survey design. The findings show that the addiction to online games was strongly correlated with dysfunctional families and poor self-control. Participants who had a poor family function and had a trouble controlling their impulses were more likely to develop an addiction to online games